KEY DIRECTIONS OF DIGITAL TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT - Zhao, Min (ФОП Косенко А. О., 2025)
At present, with the rapid development of information technology, all areas of enterprise management are gradually realizing digital transformation, and human resource management is no exception. The digital transformation of human resource management aims to use modern information technology, such as artificial intelligence, big data, cloud computing, and mobile Internet, to optimize traditional personnel management processes and improve management efficiency and decisionmaking quality.
Keywords: information technology; human resource management; digital tools; 331.108.24